Instant broth powder of mutiara catfish (Clarias gariepinus) using the spray drying method as a natural flavor enhancer - Diana Widiastuti; Siska Elisahbet Sinaga; Zahra Sahara Maharani; Eka Herlina; Ade Heri Mulyati; Farida Nuraeni; Fajar Anggraeni; Pham Van Hung (Jurnal Pendidikan Kimia (JPKIM), 2023)
"Dumbo" catfish is a type of catfish that is widely consumed and cultivated. It includes the mutiara catfish (Clarias gariepinus) growing relatively fast and having a fairly high nutritional content. It can be used as a flavor enhancer in the form of instant broth powder. This research aims to determine the formulation and best quality of instant catfish broth powder products using the Spray Drying method as a natural flavor enhancer that the public likes and follows the Indonesian National Standard. This research was started by sampling the fish and separating the meat. Then, an analysis of fish meat, including a proximate test, was prepared and continued with making broth with different recipes based on the added weight of catfish meat (in percentage) with several spices used in several formulations: 75% (F1), 70% (F2), 65% (F3), 60% (F4) and 55% (F5) by boiling and mixing all the supporting ingredients according to the predetermined formulations. Next, the drying process was carried out using the Spray Drying method, followed by an organoleptic test to obtain a chosen formula and, finally, the quality of the instant Mutiara catfish broth powder product was tested. The instant powder (F4) was the selected product based on the organoleptic test, because this formula is the most preferred product by the panelists. The results of the analysis of physical, chemical, microbiological characteristics complied with SNI 01-4218-1996 concerning broth powder. In addition, the shelf life of this product with metallized plastic packaging was 1,028.24 days.Keywords: Broth powder; Catfish; Characterization; Shelf life